2017
DOI: 10.1002/sim.7305
|View full text |Cite
|
Sign up to set email alerts
|

Mixed models, linear dependency, and identification in age‐period‐cohort models

Abstract: This paper examines the identification problem in age-period-cohort models that use either linear or categorically coded ages, periods, and cohorts or combinations of these parameterizations. These models are not identified using the traditional fixed effect regression model approach because of a linear dependency between the ages, periods, and cohorts. However, these models can be identified if the researcher introduces a single just identifying constraint on the model coefficients. The problem with such cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 29 publications
4
33
0
Order By: Relevance
“…The age of the individuals was stratified into the following groups: 18-29 years (only in the 2007-2008 period), 30-39, 40-49, 50-59, 60-79, 80-90, and 90-100 years (only in the 2017-2019 period). Data were also evaluated according to the definition of the elderly proposed by the United Nations, and the cut-off of 60 years was used to refer to the older or elderly persons (17).…”
Section: Study Design and Data Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…The age of the individuals was stratified into the following groups: 18-29 years (only in the 2007-2008 period), 30-39, 40-49, 50-59, 60-79, 80-90, and 90-100 years (only in the 2017-2019 period). Data were also evaluated according to the definition of the elderly proposed by the United Nations, and the cut-off of 60 years was used to refer to the older or elderly persons (17).…”
Section: Study Design and Data Sourcementioning
confidence: 99%
“…On the other hand, longitudinal studies involve information directly gathered in a survey of households or individuals and follow individual persons over time. Longitudinal studies allow researchers to separate the independent effects of age, period, and cohort from trends in overweight and obesity rates (17). However, large paired cohort investigations assessing anthropometric indices between long periods are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Bell and Jones (2018) showed that the data structure (e.g., the number of A, P, and C categories included in the data) affects the estimates from the RE-APC models markedly. For another example, O'Brien (2017) conjectured that assuming the effect of A, P, or C to be random produces a result similar to constraining that effect's linear trend to be near zero.…”
Section: Introductionmentioning
confidence: 99%
“…The use of parameter restrictions has often been criticized (Bell & Jones, 2013Luo & Hodges, 2016;De Ree & Alessie, 2011;O'Brien, 2017). By relying on arbitrary assumptions to reach identification, all of the studies above are likely to suffer from biases of unknown size.…”
Section: Introductionmentioning
confidence: 99%